Koguryo, The Language of Japan's Continental Relatives : an Introduction to the Historical-Comparative Study of the Japanese-Koguryoic Languages, with a Preliminary Description of Archaic Northeastern Middle Chinese. - Beckwith, Christopher I. (Brill's Japanese Studies Library, 21., 2007)
This is the first in-depth study of the extinct Koguryo language, which was once spoken in Manchuria and northern Korea. It covers the ethnolinguistic history of the Koguryo nation, philological treatment of the sources for the language, Koguryo phonology, and a complete glossary of all Archaic Koguryo and Old Koguryo words. Special attention has been given to the theory and practice of lexically-based historical-comparative linguistics. The genetic relationship of Koguryo to Japanese is shown to be secure, unlike the non-relationship of either language to Korean or 'Altaic', and much light is.